Preparation and Properties of High-Volume-Fraction SiC Reinforced Copper Matrix Composites - ZHANG Qiang, YANG Chenggang, YAO Bo, WU Jisi, QIAN Wen (Cailiao Baohu, 2022)
With the rapid development of modern industry， SiC/Cu composites have great application prospect in electronic packaging due to their excellent conductivity， high strength and thermal conductivity. In this paper， high-volume-fraction β-Sic＠Cu/Cu composites were successfully prepared by electroless plating and powder metallurgy method， and their phase， microstructure and thermal expansion coefficient were characterized by metallographic microscope， XRD and SEM. Results showed that with the increase of SiC volume fraction， the density and flexural strength of β-SiC＠Cu/Cu composites decreased， while the hardness of the composites increased. Moreover， the flexural strength of β-SiC＠Cu/Cu composites was over 70 MPa， the thermal expansion coefficient was 4.5×10-6～10.0×10-6/℃， which met the performance requirements of modern electronic packaging materials.